Low-cobalt high-temperature wear-resistant alloy prepared from CoCrMo alloy waste
Through vacuum arc smelting technology, CoCrMo alloy waste is combined with elemental materials to prepare a low-cobalt high-temperature wear-resistant alloy, which solves the problem of reuse of CoCrMo alloy waste, improves the utilization rate of waste and the recycling level of high-value metals, and achieves a win-win situation for resources and energy.
Patent Information
- Application Number
- CN202411894975.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-21
- Publication Date
- 2025-04-04
AI Technical Summary
The waste generated by CoCrMo alloy waste in the production and manufacturing process leads to the waste of high-value metals such as Co, Cr and Mo, and the existing reuse technology has problems of high energy consumption, high cost and resource waste.
By vacuum arc melting the CoCrMo alloy waste with an appropriate amount of Co, Cr, Mo, Nb, Ta, Y, W, Fe, Si, B and C, a low-cobalt high-temperature wear-resistant alloy is prepared, and the α-Co phase and ε-Co phase in the waste are high-strength and high-hard CoaMobSi/CocMod eutectic phase and in situ ceramic phase.
It significantly improves the reuse rate of CoCrMo alloy waste and the recycling and use level of high-value metal resources, reduces production costs and energy consumption, achieves a win-win situation between resources and energy, and shows excellent wear resistance in a high-temperature environment of 600-900℃.
Smart Images

Figure CN119753384A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of high-temperature wear-resistant materials, and in particular to a low-cobalt high-temperature wear-resistant alloy prepared by using CoCrMo alloy waste. Background Art
[0002] CoCrMo alloy ingots and CoCrMo parts (such as sealing rings, bearings, pipes, valves, artificial joints, dental drills and surgical instruments) will inevitably produce waste materials such as risers, sprues, runners, cutting / grinding chips, scraps and scrapped parts during the production and manufacturing process. These CoCrMo alloy wastes not only contain a large amount of strategic metals such as Co, Ni, W and Cr, but also contain rare metals such as Mo and Ti. These metals have immeasurable value both in the national defense and military level and in daily life. However, in actual production, the recovery rate of CoCrMo alloy waste is low and it is difficult to reuse, which leads to huge waste of high-value metals such as Co, Cr and Mo. The recycling technology of CoCrMo alloy waste has become a common technical problem in the precious metal and rare metal recycling industry.
[0003] At present, the commonly used methods for recycling CoCrMo alloy waste mainly include original use, combined use, downgraded use and element extraction and separation. Among them, original use and combined use are the preferred methods for waste recycling, but some waste materials (such as cutting / grinding chips and scraps, etc.) are prone to heat and oxidation during the cutting process, and the waste contains a large amount of oxides and difficult-to-remove cutting fluids and oil impurities; and for special-purpose CoCrMo alloys, such as CoCrMo alloys for aerospace and medical CoCrMo alloys, multiple remelting and processing may cause changes in the organizational structure of the waste alloy, such as grain boundary shape, grain size and carbide distribution, which in turn affects its mechanical properties and biocompatibility, making it difficult to be used in the original level or in combination. Downgraded use and element extraction and separation methods not only reduce the utilization rate of CoCrMo alloy waste and seriously waste resources, but also increase the energy consumption, cost and pollution of waste recycling exponentially, which is not in line with the sustainable development strategy. Therefore, it is urgent to propose new technologies for the recycling of CoCrMo alloy waste, improve the recycling rate of CoCrMo alloy waste and the recycling level of high-value metal resources, achieve the goal of reducing production costs and energy consumption, and achieve a win-win situation for resources and energy. Summary of the invention
[0004] In view of this, the object of the present invention is to provide a low-cobalt high-temperature wear-resistant alloy prepared from CoCrMo alloy waste. The low-cobalt high-temperature wear-resistant alloy not only realizes the matching use of CoCrMo alloy waste, but also improves the value of CoCrMo alloy waste.
[0005] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:
[0006] The present invention provides a method for preparing a low-cobalt high-temperature wear-resistant alloy, comprising the following steps: mixing raw materials in proportion and pre-placing the raw materials in a water-cooled copper crucible of a vacuum arc melting furnace, and performing vacuum arc melting to obtain the low-cobalt high-temperature wear-resistant alloy;
[0007] In terms of mass percentage, the raw materials include: 51-80% of CoCrMo alloy waste and 20-49% of single element raw materials;
[0008] The single-element raw materials include multiple ones of Co, Cr, Mo, Nb, Ta, Y, W, Fe, Si, B and C.
[0009] Preferably, the CoCrMo alloy scrap comprises the following elements in percentage by mass: 59-69% Co, 22-35% Cr, 3-9% Mo, 0.1-0.8% Mn, 0.1-0.5% C, 0.5-1.2% Si and 0.01-0.35% N.
[0010] Preferably, the CoCrMo alloy waste includes one or more of risers, sprues, runners, cuttings / grinding chips, scraps and scrap parts produced during the production process of CoCrMo alloy ingots and CoCrMo alloy joint prostheses.
[0011] Preferably, in terms of mass percentage, the single element raw materials include: Co is 0-20%, Cr is 0-11%, Mo is 1-30%, Nb is 0-10%, Ta is 0-12%, Y is 0-8%, W is 1-16%, Fe is 0.5-8.5%, Si is 0.5-4.2%, B is 0-1% and C is 0-1%, wherein Co, Cr, Nb, Ta, Y, B and C are not 0 at the same time.
[0012] Preferably, the pre-placing is to pre-place the configured raw materials in a water-cooled copper crucible in the order of metal element materials, non-metal element materials and CoCrMo alloy waste from bottom to top, and the order of adding the metal element materials is to add them in the order of melting point from low to high, from bottom to top; a piece of pure Ti block is pre-placed in another water-cooled copper crucible.
[0013] Preferably, the vacuum environment of the vacuum arc melting is achieved by repeatedly evacuating and filling with argon gas:
[0014] The first vacuuming makes the vacuum degree of the arc melting furnace reach below 2Pa, and then high-purity argon is filled for the first time to maintain the vacuum degree in the furnace below -0.1MPa; the second vacuuming makes the vacuum degree of the arc melting furnace reach 1×10 -4Pa, and then high-purity argon is filled in for the second time to maintain the vacuum degree in the furnace below -0.06MPa.
[0015] Preferably, the vacuum arc melting includes two processes:
[0016] First, pure Ti blocks are melted to eliminate residual oxygen and nitrogen in the vacuum arc melting furnace. The pure Ti blocks are melted 5 times, the current of each melting is 200-250A, and the time of each melting is 2-3 minutes.
[0017] Finally, the raw materials of the low-cobalt high-temperature wear-resistant alloy are subjected to vacuum arc melting. The low-cobalt high-temperature wear-resistant alloy is melted by electromagnetic stirring. The number of melting times is 10 to 20 times, the current of each melting is 500 to 800A, and the time of each melting is 3 to 5 minutes.
[0018] The present invention provides a low-cobalt, high-temperature wear-resistant alloy prepared by the preparation method described in the above scheme.
[0019] Preferably, the low cobalt high temperature wear-resistant alloy includes the following elements in percentage by mass: Co is 40-56%, Cr is 12-32%, Mo is 7-33%, Nb is 0-10%, Ta is 0-12%, Y is 0-8%, W is 1-16%, Fe is 0.5-8.5%, Mn is 0.08-0.64%, Si is 0.5-4.2%, B is 0-1%, C is 0.1-1.2%, and N is 0.01-0.19%.
[0020] Preferably, the low-cobalt high-temperature wear-resistant alloy has better high-temperature wear resistance at 600-900° C. than Stellite 6 alloy and Tribaloy-T400 alloy.
[0021] The invention provides a preparation method of a low-cobalt high-temperature wear-resistant alloy, comprising the following steps: mixing raw materials in proportion and pre-placing the raw materials in a water-cooled copper crucible of a vacuum arc melting furnace, and performing vacuum arc melting to obtain the low-cobalt high-temperature wear-resistant alloy; the raw materials comprise, in terms of mass percentage, 51-80% of CoCrMo alloy waste and 20-49% of single-substance raw materials; the single-substance raw materials comprise multiple types of Co, Cr, Mo, Nb, Ta, Y, W, Fe, Si, B and C.
[0022] The present invention is based on the concept of matching use, using CoCrMo alloy waste as the main raw material, and introducing appropriate single materials such as Co, Cr, Mo, Nb, Ta, Y, W, Fe, Si, B and C at the same time, so that the low hardness and non-wear-resistant α-Co phase and ε-Co phase in the CoCrMo alloy waste are transformed into high-strength, high-hardness and high-wear-resistant Co a Mo b Si / Coc Mo d Eutectic phase and in-situ ceramic phase (such as Cr 6.2 C 3.5 N 0.3 、WSi2、Fe6W6C、Nb a C b , Nb c B d and Cr e B f ), thereby obtaining a new low-cobalt high-temperature wear-resistant alloy with good high-temperature wear resistance.
[0023] On the one hand, the present invention not only allows the waste materials with low impurity content such as risers, sprues, runners and scrapped parts to be reused, but also allows the waste materials with high surface oxide content such as cutting / grinding chips and scraps to be utilized (a large amount of non-metallic elements such as C, B and Si are introduced into the present invention, and a reduction reaction occurs between the non-metallic elements and the oxides to convert the oxides into carbides (such as Cr 6.2 C 3.5 N 0.3 ) and borides (MoB4 and Cr5B3), which enhance the wear resistance of the alloy), and significantly improve the utilization rate of CoCrMo alloy waste; on the other hand, through in-situ chemical reaction, impurity elements such as Mn and N are converted into wear-resistant ceramic phases, which not only eliminates the impurity elements but also enhances the high-temperature wear resistance of the alloy. The high-temperature wear resistance of the new low-cobalt high-temperature wear-resistant alloy prepared by the present invention is better than that of conventional wear-resistant metal materials such as Stellite 6 and Tribaloy-T400 at 600-900°C, and the consumption of strategic metals such as Co is reduced. It shows broad application prospects in high-temperature fields such as aviation, aerospace, nuclear energy and metallurgy, and further improves the value of the original CoCrMo alloy.
[0024] In addition, the new low-cobalt high-temperature wear-resistant alloy provided by the present invention can be directly prepared by vacuum arc melting technology, without the need for complex thermomechanical treatment processes. The preparation process is simple and easy to operate, which significantly reduces the production cost of the alloy and enables it to have a large application market in the engineering field.
[0025] In summary, the present invention improves the recycling rate of CoCrMo alloy waste and the recycling level of high-value metal resources, obtains a new low-cobalt high-temperature wear-resistant alloy, achieves the purpose of reducing production costs, reducing energy consumption and increasing the value of CoCrMo alloy waste, and realizes a win-win situation of resources, energy and economy. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 The new low-cobalt high-temperature wear-resistant alloy Co prepared in Example 1 47.6561 Cr 25Mo 15 W9Fe1Mn 0.2341 C 0.5 Si 1. 5N 0.1098 XRD pattern of
[0027] Figure 2 The new low-cobalt high-temperature wear-resistant alloy Co prepared in Example 1 47.6561 Cr 25 Mo 15 W9Fe1Mn 0.2341 C 0.5 Si 1. 5N 0.1098 Backscattered image of microstructure at low magnification;
[0028] Figure 3 The new low-cobalt high-temperature wear-resistant alloy Co prepared in Example 1 47.6561 Cr 25 Mo 15 W9Fe1Mn 0.2341 C 0.5 Si 1. 5N 0.1098 Backscattered image of microstructure at high magnification;
[0029] Figure 4 The new low-cobalt high-temperature wear-resistant alloy Co prepared in Example 2 48.4986 Cr 15 Mo 18 Ta 6.0 Y 2.7 W 3.5 Fe 3.0 Mn 0.1746 C 0.545 Si 2.5 N 0.0818 XRD pattern of
[0030] Figure 5 The new low-cobalt high-temperature wear-resistant alloy Co prepared in Example 2 48.4986 Cr 15 Mo 18 Ta 6.0 Y 2.7 W 3.5 Fe 3.0 Mn 0.1746 C 0.545 Si 2.5 N 0.0818 Backscattered image of microstructure at low magnification;
[0031] Figure 6 The new low-cobalt high-temperature wear-resistant alloy Co prepared in Example 2 48.4986 Cr 15 Mo18 Ta 6.0 Y 2.7 W 3.5 Fe 3.0 Mn 0.1746 C 0.545 Si 2.5 N 0.0818 Backscattered image of microstructure at high magnification;
[0032] Figure 7 The new low-cobalt high-temperature wear-resistant alloy Co prepared in Example 3 45.0582 Cr 20 Mo 10 Nb 5.6166 W 10 Fe4Mn 0.221 4B 0.5 C 0.5 Si 4.0 N 0.1038 XRD pattern of
[0033] Figure 8 The new low-cobalt high-temperature wear-resistant alloy Co prepared in Example 3 45.0582 Cr 20 Mo 10 Nb 5.6166 W 10 Fe4Mn 0.221 4B 0.5 C 0.5 Si 4.0 N 0.1038 Backscattered image of microstructure at low magnification;
[0034] Fig. 9 The new low-cobalt high-temperature wear-resistant alloy Co prepared in Example 3 45.0582 Cr 20 Mo 10 Nb 5.6166 W 10 Fe4Mn 0.221 4B 0.5 C 0.5 Si 4.0 N 0.1038 Backscattered image of the microstructure at high magnification. DETAILED DESCRIPTION
[0035] The present invention provides a method for preparing a low-cobalt high-temperature wear-resistant alloy, comprising the following steps: mixing raw materials in proportion and pre-placing the raw materials in a water-cooled copper crucible of a vacuum arc melting furnace, and performing vacuum arc melting to obtain the low-cobalt high-temperature wear-resistant alloy;
[0036] In terms of mass percentage, the raw materials include: 51-80% of CoCrMo alloy waste and 20-49% of single element raw materials;
[0037] The single-element raw materials include multiple ones of Co, Cr, Mo, Nb, Ta, Y, W, Fe, Si, B and C.
[0038] In the present invention, the CoCrMo alloy waste includes but is not limited to one or more of risers, sprues, runners, cuttings / grinding chips, scraps and scrap parts produced during the production process of CoCrMo alloy ingots and CoCrMo alloy joint prostheses.
[0039] In terms of mass percentage, the CoCrMo alloy scrap preferably includes the following elements: Co is 59-69%, Cr is 22-35%, Mo is 3-9%, Mn is 0.1-0.8%, C is 0.1-0.5%, Si is 0.5-1.2%, and N is 0.01-0.35%.
[0040] In the present invention, the CoCrMo alloy waste is the main raw material in order to improve the utilization rate and economic value of the CoCrMo alloy waste.
[0041] In the present invention, the single substance raw materials include, by mass percentage, Co of 0-20%, Cr of 0-11%, Mo of 1-30%, Nb of 0-10%, Ta of 0-12%, Y of 0-8%, W of 1-16%, Fe of 0.5-8.5%, Si of 0.5-4.2%, B of 0-1% and C of 0-1%, wherein Co, Cr, Nb, Ta, Y, B and C are not 0 at the same time; preferably, Co is 0-17%, Cr is 0-6%, Mo is 5-25%, Nb is 0-7%, Ta is 0-9%, Y is 0-5%, W is 3-11%, Fe is 0.5-5.5%, Si is 0.7-3%, B is 0-0.7% and C is 0.1-0.5%, wherein Co and Cr are not 0 at the same time.
[0042] In the present invention, the role of Co, Mo and Si is to promote the formation of Co a Mo b Si / Co c Mo d Eutectic phase, Co a Mo b Si / Co c Mo d The eutectic phase has a stable structure in a high temperature environment, has high high temperature hardness and strength, and helps to improve the high temperature wear resistance of the alloy.
[0043] In the present invention, the role of Cr and Fe is to form Cr2O3 and Fe2O3 through tribochemical reaction during the friction process, thereby enhancing the high temperature wear resistance of the alloy.
[0044] In the present invention, the role of W is to improve the high temperature strength and high temperature hardness of the alloy, and to form a W-containing hard phase (WSi2 and Fe6W6C) through in-situ chemical reaction to improve the high temperature wear resistance of the alloy.
[0045] In the present invention, the non-metallic elements such as C, Si, N and B, on the one hand, exist in the alloy in the form of interstitial atoms, and exert the interstitial solid solution strengthening effect by increasing the degree of lattice distortion; on the other hand, they form wear-resistant ceramic phases with active metals such as Cr, Mo, Ta, Nb and W, thereby enhancing the mechanical properties and high-temperature wear resistance of the alloy.
[0046] In the present invention, the Mn is an inherent component in the CoCrMo alloy waste and is difficult to remove. In the present invention, by introducing non-metallic elements such as C, Si and B, in-situ reaction with Mn forms a ceramic phase, which not only eliminates the influence of Mn impurities on the mechanical properties of the material, but also helps to improve the high temperature wear resistance of the alloy.
[0047] In the present invention, the single raw material is preferably a particle or powder with a purity of ≥99.9wt%, and the CoCrMo alloy waste is directly sourced from a CoCrMo alloy foundry. All raw materials are mixed and pre-placed in a water-cooled copper crucible, and ultrasonic cleaning is required to remove impurities such as surface oil stains, and the ultrasonic cleaning is preferably performed in acetone.
[0048] In the present invention, the raw materials are preferably mixed and pre-prepared in a water-cooled copper crucible in the order of metal element materials, non-metal element materials and CoCrMo alloy waste from bottom to top, and the order of adding the metal element materials is further preferably in the order of melting point from low to high, and Co, Y, Fe, Cr, Nb, Mo, Ta and W are added in sequence from bottom to top.
[0049] In the present invention, the CoCrMo alloy waste is placed on the uppermost layer. On the one hand, the CoCrMo alloy waste has a large volume and a low melting point. During smelting, it can quickly melt and cover the non-metallic elements in the middle layer to prevent the non-metallic elements from splashing. On the other hand, there may be residual oil stains that have not been completely cleaned on the surface of the CoCrMo alloy waste. Under the extremely high temperature of the arc, these oil stains can be instantly ablated and volatilized to avoid remaining in the alloy. Non-metallic elements such as C, Si and B are placed in the middle of the metal material to prevent the non-metallic elements from splashing due to uneven heating, and to ensure that the composition of the new low-cobalt high-temperature wear-resistant alloy is consistent with that of the raw materials. The metal single substance materials are placed in order from low to high melting points and from bottom to top to ensure that the high melting point elements are completely melted without affecting the full melting of the low melting point elements.
[0050] In the present invention, the arc melting is performed in a vacuum environment, preferably in an argon atmosphere with a vacuum degree of -0.06 MPa or less.
[0051] In the present invention, the vacuum environment is preferably achieved by repeating the vacuuming and argon filling process in sequence: the first vacuuming makes the vacuum degree of the arc melting furnace reach below 2Pa, and then the first high-purity argon is filled to maintain the vacuum degree in the furnace below -0.1MPa; the second vacuuming makes the vacuum degree of the arc melting furnace reach 1×10 -4 Pa, and then high-purity argon is filled in for the second time to maintain the vacuum degree in the furnace below -0.06MPa.
[0052] In the present invention, before smelting the low-cobalt high-temperature wear-resistant alloy, it is necessary to melt the Ti block to absorb oxygen and remove nitrogen. The number of times the Ti block is smelted is preferably 5 times, the current for each smelting is preferably 200-250A, and the time for each smelting is preferably 2-3 minutes;
[0053] In the present invention, the preparation method of the novel low-cobalt high-temperature wear-resistant alloy is vacuum arc melting, preferably a composite method of vacuum arc melting and electromagnetic stirring, the number of melting times is preferably 10 to 20 times, the current for each melting is preferably 500 to 800A, the time for each melting is preferably 3 to 5 minutes, and after each melting is completed, after the alloy ingot is cooled, the ingot is preferably turned over for the next melting to ensure that the elements in the alloy are evenly distributed.
[0054] In the present invention, after arc melting is completed, the alloy ingot needs to be cooled and then taken out for use, and the cooling method is preferably to cool to room temperature with the furnace.
[0055] The present invention provides a low-cobalt, high-temperature wear-resistant alloy prepared by the preparation method described in the above scheme.
[0056] In terms of mass percentage, the low cobalt high temperature wear-resistant alloy preferably includes the following elements: Co is 40-56%, Cr is 12-32%, Mo is 7-33%, Nb is 0-10%, Ta is 0-12%, Y is 0-8%, W is 1-16%, Fe is 0.5-8.5%, Mn is 0.08-0.64%, Si is 0.5-4.2%, B is 0-1%, C is 0.1-1.2%, and N is 0.01-0.19%.
[0057] Based on the concept of matching, the present invention uses CoCrMo alloy waste as the main raw material to design and prepare a new low-cobalt high-temperature wear-resistant alloy. Compared with conventional wear-resistant metal materials Stellite 6 and Tribaloy-T400 alloy, although the low-cobalt high-temperature wear-resistant alloy of the present invention contains impurities such as Mn and N, it is converted into a wear-resistant ceramic phase through an in-situ chemical reaction, so that the new low-cobalt high-temperature wear-resistant alloy exhibits more excellent high-temperature wear resistance at 600-900°C, and reduces the consumption of strategic metal Co. The new low-cobalt high-temperature wear-resistant alloy of the present invention can be directly prepared by vacuum arc melting technology, without the need for complex processes such as thermomechanical treatment, thereby improving production efficiency, significantly reducing production costs, and showing broad application prospects in high-temperature fields such as aviation, aerospace, nuclear energy and metallurgy. In short, the present invention improves the reuse rate of CoCrMo alloy waste and the recycling level of high-value metal resources, obtains a new low-cobalt high-temperature wear-resistant alloy, achieves the purpose of reducing production costs, reducing energy consumption and increasing the value of CoCrMo alloy waste, and achieves a win-win situation for resources, energy and economy.
[0058] The low-cobalt high-temperature wear-resistant alloy prepared by using CoCrMo alloy waste provided by the present invention is described in detail below in conjunction with the embodiments, but they should not be understood as limiting the protection scope of the present invention.
[0059] Example 1
[0060] A new type of low-cobalt high-temperature wear-resistant alloy prepared from CoCrMo alloy waste has the following composition by mass percentage: 73.16% of CoCrMo alloy waste, and 26.84% of newly added single materials such as Co, Cr, Mo, W, Fe, Si and C. In detail, by mass percentage, the chemical composition of the low-cobalt high-temperature wear-resistant alloy is: Co 47.6561%, Cr 25%, Mo 15%, W 9%, Fe 1%, Mn 0.2341%, C 0.5%, Si 1.5% and N 0.1098% (Co 47.6561 Cr25Mo 15 W9Fe1Mn 0.2341 C 0.5 Si 1.5 N 0.1098 ).
[0061] Preparation method: The chemical composition of the CoCrMo alloy waste used in Example 1 is as follows by mass percentage: Co 65.135%, Cr 27.5%, Mo 5.8%, Mn 0.32%, C 0.245%, Si 0.85% and N 0.15% (i.e. Co 65.135 Cr 27.5 Mo 5.8 Mn0.32 C 0.245 Si 0.85 N 0.15 ); the newly added single-element materials, by mass percentage, are as follows: Co 0.0031%, Cr 4.881%, Mo 10.7567%, W 9%, Fe 1%, Si 0.8781% and C 0.3208%.
[0062] The CoCrMo alloy waste used in Example 1 is directly from the CoCrMo alloy foundry, in the form of risers, cuttings / grindings, scraps and scrap parts; the newly added Co, Cr, Mo, W, Fe, Si and C are particles with a purity of ≥99.9wt%. All raw materials are ultrasonically cleaned in acetone to remove impurities such as surface oil stains.
[0063] The cleaned raw materials are pre-placed in the water-cooled copper crucible of the smelting furnace in the order of metal element materials, non-metal element materials and CoCrMo alloy waste from bottom to top, and the metal element materials are added in the order of melting point from low to high, namely Co, Fe, Cr, Mo and W from bottom to top.
[0064] Vacuum arc melting is carried out in an environment with a vacuum degree of -0.06MPa. The vacuum degree is regulated by the following method: the first vacuuming is performed to make the vacuum degree of the arc melting furnace reach below 2Pa, and then high-purity argon is filled for the first time to maintain the vacuum degree in the furnace below -0.1MPa; the second vacuuming is performed to make the vacuum degree of the arc melting furnace reach 1×10 -4 Pa, and then high-purity argon is filled in for the second time to maintain the vacuum degree in the furnace below -0.06MPa.
[0065] First, the Ti block was melted for 2 minutes using a current of 230A. This process was repeated 5 times to remove residual oxygen. Then, under electromagnetic stirring, the new low-cobalt high-temperature wear-resistant alloy raw material was melted for 4.5 minutes using a current of 700A. After the alloy ingot was cooled in the furnace, it was flipped over by a mechanical arm for the next melting. This melting process was repeated 17 times to ensure that all elements were evenly distributed in the ingot. Finally, the new low-cobalt high-temperature wear-resistant alloy Co was obtained. 47.6561 Cr 25 Mo 15 W9Fe1Mn 0.2341 C 0.5 Si 1.5 N 0.1098 .
[0066] Figure 1 The new high temperature wear-resistant alloy Co prepared in Example 1 47.6561 Cr 25 Mo 15 W9Fe1Mn0.2341 C 0.5 Si 1. 5N 0.1098 The XRD pattern of Figure 1 It can be seen that the new high temperature wear-resistant alloy is mainly composed of Co3Mo2Si, CoMoSi, Co7Mo6, Co2Mo3, α-Co, ε-Co, Cr 6.2 C 3.5 N 0.3 , Fe6W6C and WSi2.
[0067] Figure 2 and Figure 3 The new high temperature wear-resistant alloy Co prepared in Example 1 is 47.6561 Cr 25 Mo 15 W9Fe1Mn 0.234 1C 0.5 Si 1.5 N 0.1098 The backscattered images of the microstructure at low and high magnifications show that the microstructure of the new high-temperature wear-resistant alloy mainly presents dendrites, and there are a large number of eutectic structures, Cr-rich phases and dispersed precipitation phases in the interdendritic regions. The dendrites and interdendritic regions contain a large amount of α-Co and ε-Co, and the main component of the eutectic structure is Co a Mo b Si(Co3Mo2Si and CoMoSi) / Co c Mo d (Co7Mo6 and Co2Mo3), the Cr-rich phase is mainly CoCrMo and Cr 6.2 C 3.5 N 0.3 The precipitated phases are mainly WSi2 and Fe6W6C.
[0068] Table 1 shows the new high temperature wear-resistant alloy Co prepared in Example 1 47.6561 Cr 25 Mo 15 W9Fe1Mn 0.2341 C 0.5 Si 1. 5N 0.1098 , Stellite 6 and Tribaloy-T400 alloys at 600°C, 800°C and 900°C. 47.6561 Cr 25 Mo 15 W9Fe1Mn 0.2341 C 0.5 Si 1.5 N 0.1098 The average wear rate at 600℃, 800℃ and 900℃ is 4.07×10-5 mm 3 ·N -1 ·m -1 , 0.0745×10 -5 mm 3 ·N -1 ·m -1 and 0.0154×10 -5 mm 3 ·N -1 ·m -1 Compared with the conventional high-temperature wear-resistant alloy Stellite-6, the wear rate is reduced by about 17.78%, 96.55% and 99.11%, respectively, and compared with Tribaloy-T400, it is reduced by 5.13%, 93.04% and 95.03%. Compared with Stellite-6 and Tribaloy-T400 alloys, the amount of cobalt element is reduced by 16.83% and 21.10%, respectively.
[0069] Table 1 New high temperature wear-resistant alloy Co 47.6561 Cr 25 Mo 15 W9Fe1Mn 0.2341 C 0.5 Si 1.5 N 0.1098 , Stellite6 and Tribaloy-T400 alloys at 600℃, 800℃ and 900℃
[0070]
[0071] Example 2
[0072] A new type of low-cobalt high-temperature wear-resistant alloy prepared from CoCrMo alloy waste has the following composition by mass percentage: 54.55% of CoCrMo alloy waste, and 45.45% of newly added single materials such as Co, Cr, Mo, Ta, Y, W, Fe, Si and C. In detail, by mass percentage, the chemical composition of the low-cobalt high-temperature wear-resistant alloy is: Co 48.4986%, Cr 15%, Mo 18%, Ta 6.0%, Y 2.7%, W 3.5%, Fe 3.0%, Mn 0.1746%, C 0.545%, Si 2.5% and N 0.0818% (Co 48.4986 Cr 15 Mo 18 Ta 6.0 Y 2.7 W 3.5 Fe 3.0 Mn 0.1746 C 0.545 Si 2.5 N0.0818 ).
[0073] Preparation method: The chemical composition of the CoCrMo alloy waste used in Example 2 is as follows by mass percentage: Co 65.135%, Cr 27.5%, Mo 5.8%, Mn 0.32%, C 0.245%, Si 0.85% and N 0.15% (i.e. Co 65.135 Cr 27.5 Mo 5.8 Mn 0.32 C 0.245 Si 0.85 N 0.15 ); newly added single-element materials, by mass percentage, the specific composition is: Co12.9675%, Mo 14.8361%, Ta 6.0%, Y 2.7%, W 3.5%, Fe2.0%, Si 2.0363% and C0.4114%.
[0074] The CoCrMo alloy waste used in Example 2 is directly from the CoCrMo alloy foundry, in the form of risers, cuttings / grindings, scraps and scrap parts; the newly added Co, Mo, W, Fe, Si and C are particles with a purity of ≥99.9wt%. All raw materials are ultrasonically cleaned in acetone to remove impurities such as surface oil stains.
[0075] The cleaned raw materials are pre-placed in the water-cooled copper crucible of the smelting furnace in the order of metal element materials, non-metal element materials and CoCrMo alloy waste from bottom to top, and the metal element materials are added in the order of melting point from low to high, namely Co, Y, Fe, Mo, Ta and W from bottom to top.
[0076] Vacuum arc melting is carried out in an environment with a vacuum degree of -0.06MPa. The vacuum degree is regulated by the following method: the first vacuuming is performed to make the vacuum degree of the arc melting furnace reach below 2Pa, and then high-purity argon is filled for the first time to maintain the vacuum degree in the furnace below -0.1MPa; the second vacuuming is performed to make the vacuum degree of the arc melting furnace reach 1×10 -4 Pa, and then high-purity argon is filled in for the second time to maintain the vacuum degree in the furnace below -0.06MPa.
[0077] First, the Ti block was melted for 2 minutes using a current of 230A. This process was repeated 5 times to remove residual oxygen. Then, under electromagnetic stirring, the new low-cobalt high-temperature wear-resistant alloy raw material was melted for 5.0 minutes using a current of 760A. After the alloy ingot was cooled in the furnace, it was flipped over by a mechanical arm for the next melting. This melting process was repeated 15 times to ensure that all elements were evenly distributed in the ingot. Finally, the new low-cobalt high-temperature wear-resistant alloy Co was obtained. 48.4986 Cr15 Mo 18 Ta 6.0 Y 2.7 W 3.5 Fe 3.0 Mn 0.1746 C 0.545 Si 2.5 N 0.0818 .
[0078] Figure 4 The new high temperature wear-resistant alloy Co described in Example 2 48.4986 Cr 15 Mo 18 Ta 6.0 Y 2.7 W 3.5 Fe 3.0 Mn 0.174 6C 0.545 Si 2.5 N 0.0818 The XRD pattern of Figure 1 It can be seen that the new high temperature wear-resistant alloy is mainly composed of Co3Mo2Si, CoMoSi, Co7Mo6, Co2Mo3, α-Co, ε-Co, Cr 6.2 C 3.5 N 0.3 And WSi2.
[0079] Figure 5 and Figure 6 The new high temperature wear-resistant alloy Co prepared in Example 2 48.4986 Cr 15 Mo 18 Ta 6.0 Y 2.7 W 3.5 Fe 3.0 Mn 0.1746 C 0.545 Si 2.5 N 0.0818 From the backscattered images of the microstructure at low and high magnifications, the microstructure of the novel high temperature wear-resistant alloy mainly presents dendrites, interdendritic structures and eutectic structures.
[0080] Table 2 shows the new high temperature wear-resistant alloy Co prepared in Example 2 48.4986 Cr 15 Mo 18 Ta 6.0 Y 2.7 W 3.5 Fe 3.0 Mn 0.174 6C 0.545 Si 2.5 N 0.0818, Stellite 6 and Tribaloy-T400 alloys at 600°C, 800°C and 900°C. 48.4986 Cr 15 Mo 18 Ta 6.0 Y 2.7 W 3.5 Fe 3.0 Mn 0.1746 C 0.545 Si 2.5 N 0.0818 The average wear rate at 600℃, 800℃ and 900℃ is 1.41×10 -5 mm 3 ·N -1 ·m -1 , 0.026×10 -5 mm 3 ·N -1 ·m -1 and 0.25×10 - 5 mm 3 ·N -1 ·m -1 Compared with the conventional high temperature wear-resistant alloy Stellite-6, the wear rates were reduced by 71.52%, 98.82% and 82.08%, respectively, and compared with Tribaloy-T400, the wear rates were reduced by 67.13%, 97.62% and 19.03%, respectively. Compared with Stellite-6 and Tribaloy-T400 alloys, the amount of cobalt element was reduced by about 15.36% and 19.70%, respectively.
[0081] Table 2 New high temperature wear-resistant alloy Co 48.4986 Cr 15 Mo 18 Ta 6.0 Y 2.7 W 3.5 Fe 3.0 Mn 0.1746 C 0.545 Si 2.5 N 0.0818 Wear rates of Stellite 6 and Tribaloy-T400 alloys at 600℃, 800℃ and 900℃
[0082]
[0083] Example 3
[0084] A new type of low-cobalt high-temperature wear-resistant alloy prepared from CoCrMo alloy waste has the following composition by mass percentage: CoCrMo alloy waste is 69.18%, and newly added single materials such as Co, Cr, Mo, W, Fe, Si and C account for a total of 30.82%. In detail, by mass percentage, the chemical composition of the low-cobalt high-temperature wear-resistant alloy is: Co 45.0582%, Cr 20%, Mo 10%, Nb 5.6166%, W 10.0%, Fe 4.0%, Mn 0.2214%, B 0.5%, C 0.5%, Si4.0% and N 0.1038% (Co 45.0582 Cr 20 Mo 10 Nb 5.6166 W 10 Fe4Mn 0.2214 B 0.5 C 0.5 Si 4.0 N 0.1038 ).
[0085] Preparation method: The chemical composition of the CoCrMo alloy waste used in Example 3 is as follows by mass percentage: Co 65.135%, Cr 27.5%, Mo 5.8%, Mn 0.32%, C 0.245%, Si 0.85% and N 0.15% (i.e. Co 65.135 Cr 27.5 Mo 5.8 Mn 0.32 C 0.245 Si 0.85 N 0.15 ); the newly added single-element materials, by mass percentage, are as follows: Cr0.9755%, Mo 5.9876%, Nb 5.6166%, W 10.0%, Fe 4.0%, B 0.5%, Si 3.412% and C0.3305%.
[0086] The CoCrMo alloy waste used in Example 3 is directly from the CoCrMo alloy foundry, in the form of risers, cuttings / grindings, scraps and scrap parts; the newly added Cr, Mo, Nb, W, Fe, B, Si and C are particles with a purity of ≥99.9wt%. All raw materials are ultrasonically cleaned in acetone to remove impurities such as surface oil stains.
[0087] The cleaned raw materials are pre-placed in the water-cooled copper crucible of the smelting furnace in the order of metal element materials, non-metal element materials and CoCrMo alloy waste from bottom to top, and the metal element materials are added in the order of melting point from low to high, namely Fe, Cr, Nb, Mo and W from bottom to top.
[0088] Vacuum arc melting is carried out in an environment with a vacuum degree of -0.06MPa. The vacuum degree is regulated by the following method: the first vacuuming is performed to make the vacuum degree of the arc melting furnace reach below 2Pa, and then high-purity argon is filled for the first time to maintain the vacuum degree in the furnace below -0.1MPa; the second vacuuming is performed to make the vacuum degree of the arc melting furnace reach 1×10 -4 Pa, and then high-purity argon is filled in for the second time to maintain the vacuum degree in the furnace below -0.06MPa.
[0089] First, the Ti block was melted for 2 minutes using a current of 230A. This process was repeated 5 times to remove residual oxygen. Then, under electromagnetic stirring, the new low-cobalt high-temperature wear-resistant alloy raw material was melted for 5.0 minutes using a current of 680A. After the alloy ingot was cooled in the furnace, it was flipped over by a mechanical arm for the next melting. This melting process was repeated 20 times to ensure that all elements were evenly distributed in the ingot. Finally, the new low-cobalt high-temperature wear-resistant alloy Co was obtained. 45.0582 Cr 20 Mo 10 Nb 5.6166 W 10 Fe4Mn 0.221 4B 0.5 C 0.5 Si 4.0 N 0.1038 .
[0090] Figure 7 The new high temperature wear-resistant alloy Co prepared in Example 3 45.0582 Cr 20 Mo 10 Nb 5.6166 W 10 Fe4Mn 0.2214 B 0. 5C 0.5 Si 4.0 N 0.1038 The XRD pattern of Figure 1 It can be seen that the new high temperature wear-resistant alloy is mainly composed of Co3Mo2Si, CoMoSi, Co7Mo6, Co2Mo3, α-Co, ε-Co, Cr 6.2 C 3.5 N 0.3 , WSi2, Nb2C, Nb3B2, MoB4 and Cr5B3.
[0091] Figure 8 and Fig. 9 The new high temperature wear-resistant alloy Co prepared in Example 3 45.0582 Cr 20 Mo 10 Nb 5.6166 W 10 Fe4Mn0.221 4B 0.5 C 0.5 Si 4.0 N 0.1038 From the backscattered images of the microstructure at low and high magnifications, the microstructure of the novel high-temperature wear-resistant alloy mainly presents dendrites, interdendritic structures, in-situ precipitation phases and eutectic structures.
[0092] Table 3 shows the new high temperature wear-resistant alloy Co prepared in Example 3 45.0582 Cr 20 Mo 10 Nb 5.6166 W 10 Fe4Mn 0.2214 B 0. 5C 0.5 Si 4.0 N 0.1038 , Stellite 6 and Tribaloy-T400 alloys at 600°C, 800°C and 900°C. 45.0582 Cr 20 Mo 10 Nb 5.6166 W 10 Fe4Mn 0.2214 B 0.5 C 0.5 Si 4.0 N 0.1038 The average wear rate at 600℃, 800℃ and 900℃ is 4.21×10 -5 mm 3 ·N -1 ·m -1 , 0.095×10 -5 mm 3 ·N -1 ·m -1 and 0.24×10 - 5 mm 3 ·N -1 ·m -1 Compared with the conventional high temperature wear-resistant alloy Stellite-6, the wear rate is reduced by about 14.95%, 95.60% and 86.13% respectively, and compared with Tribaloy-T400, it is reduced by 1.86%, 91.12% and 22.58% respectively. And compared with Stellite-6 and Tribaloy-T400 alloys, the amount of cobalt element is reduced by 21.36% and 25.40% respectively.
[0093] Table 3 New high temperature wear-resistant alloy Co 45.0582 Cr 20 Mo 10 Nb5.6166 W 10 Fe4Mn 0.2214 B 0.5 C 0.5 Si 4.0 N 0.1038 Wear rates of Stellite 6 and Tribaloy-T400 alloys at 600℃, 800℃ and 900℃
[0094]
[0095] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A method for preparing a low-cobalt high-temperature wear-resistant alloy, characterized in that: The method comprises the following steps: mixing the raw materials in proportion and pre-placing the raw materials in a water-cooled copper crucible of a vacuum arc melting furnace, and performing vacuum arc melting to obtain the low-cobalt high-temperature wear-resistant alloy; Calculated by mass percentage, the raw materials include: 51-80% of CoCrMo alloy waste and 20-49% of single element raw materials; The single-element raw materials include multiple ones of Co, Cr, Mo, Nb, Ta, Y, W, Fe, Si, B and C.
2. The preparation method according to claim 1, characterized in that: The CoCrMo alloy scrap includes the following elements in terms of mass percentage: Co is 59-69%, Cr is 22-35%, Mo is 3-9%, Mn is 0.1-0.8%, C is 0.1-0.5%, Si is 0.5-1.2%, and N is 0.01-0.35%.
3. The preparation method according to claim 1 or 2, characterized in that: The CoCrMo alloy waste includes one or more of risers, sprues, runners, cutting / grinding chips, scraps and scrap parts produced during the production process of CoCrMo alloy ingots and CoCrMo alloy joint prostheses.
4. The preparation method according to claim 1, characterized in that: In terms of mass percentage, the single-element raw materials include: Co is 0-20%, Cr is 0-11%, Mo is 1-30%, Nb is 0-10%, Ta is 0-12%, Y is 0-8%, W is 1-16%, Fe is 0.5-8.5%, Si is 0.5-4.2%, B is 0-1% and C is 0-1%, wherein Co, Cr, Nb, Ta, Y, B and C are not 0 at the same time.
5. The preparation method according to claim 1, characterized in that: The pre-placing is to pre-place the configured raw materials in a water-cooled copper crucible in the order of metal single material, non-metal single material and CoCrMo alloy waste from bottom to top, and the order of adding the metal single material is to add it in the order of melting point from low to high, from bottom to top; a piece of pure Ti block is pre-placed in another water-cooled copper crucible.
6. The preparation method according to claim 1, characterized in that: The vacuum environment of the vacuum arc melting is achieved by repeatedly evacuating and filling with argon gas: The first vacuuming makes the vacuum degree of the arc melting furnace reach below 2Pa, and then high-purity argon is filled for the first time to maintain the vacuum degree in the furnace below -0.1MPa; the second vacuuming makes the vacuum degree of the arc melting furnace reach 1×10 -4 Pa, and then high-purity argon is filled in for the second time to maintain the vacuum degree in the furnace below -0.06MPa.
7. The preparation method according to claim 5, characterized in that: The vacuum arc melting includes two processes: First, pure Ti blocks are melted to eliminate residual oxygen and nitrogen in the vacuum arc melting furnace. The pure Ti blocks are melted 5 times, the current of each melting is 200-250A, and the time of each melting is 2-3 minutes. Finally, the raw materials of the low-cobalt high-temperature wear-resistant alloy are subjected to vacuum arc melting. The low-cobalt high-temperature wear-resistant alloy is melted by electromagnetic stirring. The number of melting times is 10 to 20 times, the current of each melting is 500 to 800A, and the time of each melting is 3 to 5 minutes.
8. The low-cobalt, high-temperature wear-resistant alloy prepared by the preparation method according to any one of claims 1 to 7.
9. The low-cobalt high-temperature wear-resistant alloy according to claim 8, characterized in that: The low cobalt high temperature wear-resistant alloy includes the following elements in percentage by mass: Co is 40-56%, Cr is 12-32%, Mo is 7-33%, Nb is 0-10%, Ta is 0-12%, Y is 0-8%, W is 1-16%, Fe is 0.5-8.5%, Mn is 0.08-0.64%, Si is 0.5-4.2%, B is 0-1%, C is 0.1-1.2%, and N is 0.01-0.19%.
10. The low-cobalt high-temperature wear-resistant alloy according to claim 9, characterized in that: The low-cobalt high-temperature wear-resistant alloy has better high-temperature wear resistance at 600-900° C. than Stellite 6 alloy and Tribaloy-T400 alloy.